COMPARISON OF SAFETY AND EFFICACY OF PNEUMATIC VERSUS LASER LITHOTRIPSY IN URETERIC STONES - Muhammad Saddiq Haris; Syed Atif Hussain; Rana Ata ur Rehman; Khizar Hayat Gondal; Ali Shandar Durrani; Muhammad Raheem Sajjad (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Treatments for ureteral calculi evolve, over the past decades from open ureterolithotomy to minimally invasive procedures. Objective of this study is to compare the efficacy of pneumatic versus laser lithotripsy in ureteric stones. METHODOLGY: A randomized controlled trial was conducted in Department of Urology Sir Ganga Ram Hospital, Lahore from 1st March 2018 to 31st August 2018. Patients were divided into two groups. In group A, 2 Fr pneumatic probe was used for pneumatic lithotripsy, while in group B, 550 μm fiber probe was used for laser lithotripsy. RESULTS: Efficacy of Group A (pneumatic lithotripsy) was seen in 57 (77.63%) patients while in Group B (laser lithotripsy) was seen in 71 (93.42%) patients with p-value of 0.006 CONCLUSION: Laser lithotripsy in ureteric stones is better as compared to pneumatic lithotripsy.